A Career of Unyielding Exploration: In Memory of Ion C. Baianu (1947-2013) - Ronald Brown; James F. Glazebrook (Quanta)
We were deeply saddened to learn of the sudden death of our colleague, friend, and member of the Editorial Board of Quanta, Professor Ion C. Baianu, who unexpectedly passed away in Urbana, Illinois, USA, on February 10, 2013. Ion left behind his wife, Kimiko, his son, Stephen, and daughters, Antonia and Christina. He also left behind the achievements of a profound and illustrious career in his chosen fields of biophysics, spectroscopy, food science, and bioengineering.